Analysis of the distribution of international migration based on pushing and pulling factors of migration in Watulimo District, Trenggalek Regency - Qoriandini Qoriandini; Sri Astutik; Elan Artono Nurdin (Universitas Negeri Malang, 2024)
This study was motivated by the high number of people in Watulimo Subdistrict, Trenggalek Regency, who have undertaken international migration. They mostly stay abroad not just for one or two years but for years. This study analyzes the distribution of international migration based on the push and pull factors of migration. This research was conducted in Watulimo District, Trenggalek Regency using quantitative research methods type hypotheses or explanatory research. The data analysis was carried out using the logit method (binary logistic regression). The results show that the distribution of international migration in Watulimo District is spread over twelve villages, with the most significant driving factors being land ownership and the pull factors. The pull factors contain income and the desired job opportunities in the destination area, as evidenced by the significant value of land ownership is 0.045, the income is 0.000, and the presence of desired jobs in the destination area, with a significant value of 0.005. Those factors have a lower than 0.05 significant value, suggesting their significant influences on international migration.